Psychological symptoms and body image in individuals with gender dysphoria: A comparison between Iranian and Dutch clinics - Shirdel-Havar, Esmail (Int J Transgend, 2018)
Background: Few studies have compared the psychological functioning of individuals with gender dysphoria in Western and non-Western cultures. To our knowledge, this is the first study comparing the mental health of transgender individuals from an Islamic and non-Islamic country (Iran and the Netherlands). Methods: In this study, the psychological functioning and body image of 163 individuals with gender dysphoria (100 transgender women (75 in the Netherlands, 25 in Iran) and 63 transgender men (45 in the Netherlands, 18 in Iran) in two clinics located in Iran (N = 43) and the Netherlands (N = 120) was evaluated using the SCL-90 and the Body Image Scale (BIS). Also, none of these individuals had yet received hormonal therapy and/or surgery in their clinics. Results: Dutch participants (M = 31.56, SD = 12.26) were older than Iranian participants (M = 25.21, SD = 3.04). Dutch transwomen were less often androphilic (sexually attracted to men) than Iranian transwomen, and Iranian trans people were more often bisexual than the Dutch trans people. Significantly more Dutch transgender people were married (we had no information about the gender of the spouse), and indicated to have more contact with their families than the participants in Iran. The participants from Iran had significantly more psychological complaints than the Dutch participants. Compared to participants in Iran, participants in the Netherlands were more dissatisfied with their secondary sexual characteristics and neutral body characteristics, but there was no significant difference between the countries in terms of satisfaction with primary sex characteristics. Conclusions: Although transgender people in many countries face social and mental health problems, this study suggests that socio-cultural factors may increase the likelihood of psychopathology.